Identification and hierarchical structure of critical success factors for innovation in construction projects: Chinese perspective - Liu, Hui; Skibniewski, Miroslaw J.; Wang, Mengjun (Journal of Civil Engineering and Management, 2016)
This paper identifies 20 critical success factors (CSFs) of innovation in China’s construction projects through literature review, a case study and expert interviews. Integrated Structural Modeling (ISM) and MICMAC (Impact Matrix Cross-reference Multiplication Applied to a Classification) analysis were used to hierarchically structure CSFs as well as to analyze their inter-relationships. The dependence and driver power of each factor were also analyzed. By doing this, this paper presents structural clarity and establishes a hierarchical order for prioritization for the decision-making. The findings show that most of the CSFs (19 out of 20) have strong inter-relationships. According to the law of vital few and trivial many, 80% of effects come from 20% of the causes for many events. This paper suggests that intensive effort should focus on the root source of CSFs: owner’s involvement and leadership, top management commitment, and strategic importance of the innovation project. Besides, external support, which is beyond the innovation project network, plays an important role in the success of innovation in China’s construction projects.First published online: 03 Nov 2015